Obtención de astaxantina a partir de residuos de camarón fermentados - Armenta López, Roberto Emeterio (Universidad Autónoma Metropolitana, 2002)
The objective of this thesis was to study various aspects on carotenoprotein extraction from shrimp residues, treated by enzymatic means in order to split the protein and pigment moieties. Purification and concentration of these two components by a membrane process in an enzymatic bioreactor was also studied. Shrimp residues were subjected to lactic fermentation as a stabilizing method. Carotenoproteins were then extracted using a petroleum ether:acetone:water (1 5:75:19) system. The protein-pigment complex was dissolved in phosphate buffer. Four enzymatic treatments were tested: protease, protease:lipase, cellulase and ce1lulase:lipase. The efficiency of each treatment was evaluated by the amount of soluble protein and total xanthophylls in the extract. A treatment with a protease was carried out using 15 and 20 UP at pH 7 or 8 during 24 hours. The highest carotene and protein concentrations were obtained using 20 UP at pH 8 during 24 hours. The most efficient protease:lipase treatment, in terms of protein:pigment separation, was observed when a 15:lO (UP:UL) ratio was used during 12 hours. When 20 BG cellulase were applied for 24 hours at pH 5, the complex almost entirely dissociated; this splitting was improved when 20:lO (BG:UL) ratio was applied for 24 hours. Fifteen and 20 UP were applied on carotenoproteins dissolved into two solvent proportions, 15:75:1 O and 156525; when 20 UP were used in the 156525 solvent system during 24 hours, 83.1% of the pigments obtained as compared to the protease:lipase treatment on phosphate buffer. The hydrolysis of carotenoproteins with a protease was also studied in a membrane enzymatic bioreactor. Fifteen and 20 UP were applied during 16 hours; 83% of pigments were obtained when 20 UP were used during 14 hours, as compared to a hydrolysis using 15 UP for 24 hours in a model system. The volume concentration factor, using an ultrafiltration membrane, was 8.27 for soluble protein in the retentate; the concentration in the permeate by reverse osmosis of the pigments was 4.66. Carotenoprotein extraction yields were (mg / kg residue): 272.2 by solvent extraction; 1100-1 140 by hydrolysis with a protease; 1567 with a protease:lipase system, 1302 with a protease in an organic solvent; 769.7 with a cellulase; and 91 1.9 with a protease in a membrane enzymatic bioreactor. The pigment extracted from shrimp residues, a commercial synthetic pigment (Carophyll pinkMR) and 11 pigment standards were analyzed using an HPLC fitted with a reverse phase column; retention times and calibration curves were obtained. Values for astaxanthin and astacene were used as a reference for pigment stability; this was carried out during 8 weeks studying the effect of daylight, temperature and oxygen availability on astaxanthin degradation due to oxidation and subsequent astacene formation. Results showed that the natural pigment oxidized in a higher degree than the synthetic pigment. Daylight and high temperatures were the two most significant conditions in promoting astaxanthin oxidation. When factor interactions were considered, the most intense degradation occurred at daylight-high oxygen-high temperature conditions. Treatments including daylight and high oxygen were consistently the most oxidative ones. Amino-acid composition of the carotenoprotein obtained from fermented and nonfermented residues was studied. Carotenoproteins obtained for these two methods were rich in aspartate, glutamate and the essential amino-acids leucine and lysine. Carotenoproteins from fermented residues had higher concentration of phenylalanine, histidine, threonine and tryptophane; arginine and valine levels were higher in nonfermented residues. The molecular weight of the protein moiety was 260 kDa and it was obtained by electrophoresis. High concentrations of astaxanthin can be obtained by lactic fermentation followed by an enzymatic hydrolysis. This combined process is feasible to be applied to high shrimp residue volumes, such as those obtained in Mexico. The process can be carried out in a membrane enzymatic bioreactor recovering pigments and high protein concentrations. It is suggested that future studies in this topic will envisage enzymatic hydrolysis of carotenoproteins in a bioreactor, using protease:lipase and cellulase:lipase systems. Finally, considerations on process scaling-up as well as on improving pigment stability by polymer (excipient) and antioxidant addition are recommended for future studies.; La presente tesis aborda estudios sobre carotenoproteínas extraídas de residuos de camarón fermentados, las cuales fueron sujetas a distintos tratamientos de hidrólisis para separar a la proteína y los pigmentos que la forman, purificando y concentrando estos componentes a través de procesos de membrana adaptados en un bioreactor enzimático. Los residuos de camarón fueron sometidos a fermentación láctica como método de estabilización, para después extraer las carotenoproteínas por medio de un sistema de disolventes orgánicos compuesto de éter de petró1eo:acetona:agua (1 5:75:1 O). El complejo pigmento-proteína se disolvió en búfer de fosfatos y se aplicaron diversos tratamientos enzimáticos con proteasa, proteasa:lipasa, celulasa y celulasa:lipasa, evaluándose el nivel de hidrólisis sobre la base de proteína soluble y xantofilas totales. El primero de ellos, con una proteasa, se llevó a cabo con 15 y 20 UP, pH 7 y 8 a lo largo de 24 horas de experimento, obteniendo la mayor iiberación de carotenos y proteína soluble con 20 UP, pH 8 por 24 horas. El tratamiento proteasa:lipasa más eficiente fue con 1510 (UP:UL) por 12 horas, este proceso enzimático logró el mayor grado de separación de pigmentos y proteína. Con 20 BG de celulasa por 24 horas a pH 5 se consiguió disociar el complejo, logrando'mejorar la separación sin hidrólisis proteica con el tratamiento 20:lO (BG:UL) por 24 horas. Se desarrolló la hidrólisis con 15 y 20 UP de proteasa sobre carotenoproteínas disueltas en dos proporciones del sistema de disolventes, 157510 y 15:65:25. Con 20 UP por 24 horas en la segunda proporción se alcanzó 83.1 % en relación a los pigmentos liberados en búfer de fosfatos con proteasa:lipasa. La hidrólisis de carotenoproteínas con la proteasa también se desarrolló en un bioreactor enzimático de membrana probando 15 y 20 UP durante 16 horas de proceso; con 20 UP por 14 horas se logró 83% de liberación de pigmentos sobre la base de lo alcanzado con 15 UP por 24 horas en sistema modelo; se obtuvo un factor de concentración volumétrico de 8.27 para la proteína soluble retenida por membrana de ultrafiltración y los pigmentos del permeado se concentraron 4.66 veces en volumen por medio ósmosis inversa. Los rendimientos de extracción de carotenoides en mg por kilogramo de residuo de camarón fermentado fueron: 272.2 en el extracto con disolventes, 1100-1 140 con tratamientos con proteasa, 1567 con proteasa:lipasa, 1302 con proteasa en disolventes orgánicos, 769.7 con celulasa, 905.9 con celulasa:lipasa, y 91 1.9 con proteasa en el bioreactor enzimático de membrana. El pigmento extraído de camarón, y un pigmento sintético comercial (Carophyll pinkMR), además de 11 estándares de pigmentos, fueron analizados en HPLC en columna de fase reversa obteniendo los tiempos de retención y curvas de calibración de la concentración, de las cuales se utilizaron las correspondientes a astaxantina y astaceno para el estudio de estabilidad de pigmentos. Este se llevó a cabo durante 8 semanas evaluando el efecto de la luz, temperatura y oxígeno sobre la degradación por oxidación de astaxantina y la consecuente formación de astaceno, resultando una mayor oxidación del pigmento natural en comparación con el pigmento sintético . comercial; la luz y temperatura alta son las condiciones que mayor efecto de oxidación tienen en la astaxantina. Con respecto a la interacción de factores la mayor degradación se presentó con luz-oxígeno-temperaturas altas, observando una constante en mayor grado de oxidación con los tratamientos que combinaron el efecto de luz y oxígeno. Se determinó la composición de aminoácidos en carotenoproteínas de residuos de camarón fermentados y no fermentados. Se encontró que las carotenoproteínas obtenidas por los dos métodos son ricas en aspartato, glutamato y los aminoácidos esenciales leucina y lisina. Las carotenoproteínas de residuos fermentados tuvieron mayor cantidad de fenilalanina, histidina, treonina y triptófano. Los niveles de arginina y valina fueron mayores en carotenoproteínas de residuos no fermentados. Finalmente, por electroforesis se obtuvo un peso molecular de 260 kDa para la parte proteica resultante de la disociación de carotenoproteínas. Por medio de la fermentación láctica e hidrólisis enzimática se pueden obtener altas concentraciones de astaxantina a partir de los grandes volúmenes de residuos de camarón producidos en México, proceso realizable en bioreactor enzimático de membrana, donde además de pigmentos se recuperan cantidades importantes de proteína. Se sugieren estudios a futuro sobre la hidrólisis enzimática de carotenoproteínas en el bioreactor mediante el tratamiento proteasa:lipasa y celulasa:lipasa, además de las consideraciones necesarias para aumentar la escala del proceso, y finalmente, mejorar la estabilidad del producto final con el uso de antioxidantes y vehículos o excipientes (polímeros) que den forma y protección a los pigmentos.